Degradable PP protective film with enhanced weather resistance

By designing a weather-resistance enhancement system and a PP protective film with a degradable matrix, the problems of poor weather resistance and difficulty in degradation of traditional PP protective films are solved, and the long-term stable performance and controllable degradation effect in the natural environment are achieved, which significantly improves the overall performance of the material.

CN120173420APending Publication Date: 2025-06-20ZHEJIANG JINSHENG DEOCRATION MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510549293.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2025-06-20

AI Technical Summary

Technical Problem

Traditional PP protective films have poor weather resistance and are difficult to degrade, resulting in a shortened service life in natural environments and a “white pollution”.

Method used

A degradable PP protective film with enhanced weather resistance was designed. By combining a special weather resistance enhancement system and a degradable matrix, an optimized processing technology is adopted to ensure that the protective film maintains stable performance in long-term outdoor use and achieves controllable degradation in the natural environment.

Benefits of technology

It achieves excellent weather resistance and efficient degradability, which is significantly better than commercially available products, meets high-end packaging and protection needs, while being both environmentally friendly and economical.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120173420A_ABST
    Figure CN120173420A_ABST
Patent Text Reader

Abstract

The invention discloses a degradable PP (polypropylene) protective film with enhanced weather resistance. The degradable PP material is prepared from the following raw materials in parts by weight: 55 to 65 parts of degradable PP resin, 9 to 12 parts of nano titanium dioxide / graphene composite powder, 6 to 7 parts of silane coupling agent modified hindered amine light stabilizer, 6 to 9 parts of acetyl tributyl citrate, 1.5 to 2.5 parts of zinc stearate and ethylene bis stearamide compound lubricant and 1 to 2 parts of hindered phenol and phosphite antioxidant compound. And 0.5 to 1.5 parts of lipase immobilized microcapsules. The PP protective film has the beneficial effect that the weather resistance and the degradability are synergistically improved. By designing a special weather-resistant reinforcing system and a degradable matrix and combining with an optimized processing technology, the protective film keeps stable performance in long-term outdoor use, and has the advantage of controllable degradation in a natural environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and more specifically, to the improvement of degradable PP protective films. Background Art

[0002] Polypropylene (PP) occupies an important position in the field of protective films due to its excellent mechanical properties, good processability, and low cost. However, traditional PP protective films have two key defects: First, poor weather resistance. Under the action of natural environments such as ultraviolet rays, high temperature, and humidity, the PP molecular chains are prone to oxidation breakage, cross-linking and other reactions, resulting in the yellowing, embrittlement of the film material, and the decline of mechanical properties, shortening the service life; Second, it is difficult to degrade. After being discarded, it remains in the natural environment for a long time, forming "white pollution" and seriously damaging the ecological balance.

[0003] In the prior art, the methods to improve the weather resistance of PP films mainly include adding additives such as ultraviolet absorbers and hindered amine light stabilizers, but there are problems such as the migration of additives, uneven dispersion, and the attenuation of long-term protection effects; while the development of degradable PP materials mainly focuses on simply introducing biodegradable components, without fully considering the synergistic optimization of weather resistance and degradation performance, resulting in the comprehensive performance of the materials being difficult to meet the actual application requirements. Summary of the Invention

[0004] (1) Technical Problems to be Solved

[0005] Aiming at the deficiencies of the prior art, the present invention provides a degradable PP protective film with enhanced weather resistance, which realizes the synergistic improvement of weather resistance and degradability. By designing a special weather resistance enhancement system and a degradable matrix, combined with an optimized processing technology, the protective film maintains stable performance during long-term outdoor use, and at the same time realizes the advantage of controllable degradation in the natural environment, thereby solving the problems in the above background art.

[0006] (2) Technical Solutions

[0007] To achieve the above-mentioned PP protective film that realizes the synergistic improvement of weather resistance and degradability. By designing a special weather resistance enhancement system and a degradable matrix, combined with an optimized processing technology, the protective film maintains stable performance during long-term outdoor use, and at the same time realizes the advantage of controllable degradation in the natural environment, the specific technical solutions adopted by the present invention are as follows: A degradable PP protective film with enhanced weather resistance is composed of the following raw materials in parts by weight: 55 - 65 parts of degradable PP resin, 9 - 12 parts of nano titanium dioxide / graphene composite powder, 6 - 7 parts of silane coupling agent modified hindered amine light stabilizer, 6 - 9 parts of tributyl acetylcitrate, 1.5 - 2.5 parts of a compound lubricant of zinc stearate and ethylene bisstearamide, 1 - 2 parts of a compound of hindered phenol and phosphite antioxidants, and 0.5 - 1.5 parts of lipase immobilized microcapsules.

[0008] The degradable PP resin is a graft copolymer of polylactic acid and PP, with a grafting rate of 3%-8%. The graft copolymer is prepared by a melt grafting process, and in the melt grafting process, the initiator is benzoyl peroxide, and its dosage is 0.5%-1.5% of the total mass of PP and PLA.

[0009] In the nano-titanium dioxide / graphene composite powder, the mass ratio of nano-titanium dioxide to graphene is 3:1. The particle size of the nano-titanium dioxide is 20-50 nm, and the number of layers of the graphene is 1-3 layers.

[0010] The silane coupling agent-modified hindered amine light stabilizer is prepared by reacting a hindered amine light stabilizer with a silane coupling agent in an organic solvent at 60-80 °C for 2-4 hours. The mass ratio of the hindered amine light stabilizer to the silane coupling agent is 1:(0.1-0.3).

[0011] The acid value of the tributyl acetylcitrate is ≤0.2 mgKOH / g, and the chromaticity (APHA) is ≤20.

[0012] In the compound lubricant of zinc stearate and ethylene bisstearamide, the mass ratio of zinc stearate to ethylene bisstearamide is 2:1. The purity of the zinc stearate is ≥99%. The melting point of ethylene bisstearamide is 141-146 °C. In the compound of hindered phenol antioxidant and phosphite antioxidant, the hindered phenol antioxidant is antioxidant 1076, and the phosphite antioxidant is antioxidant 168. The mass ratio of the two is (0.6-1.2):(0.4-0.8).

[0013] The lipase-immobilized microcapsules are prepared by emulsion polymerization. The wall material used in the emulsion polymerization is sodium alginate and chitosan. The mass ratio of sodium alginate to chitosan is (1-3):1. The particle size of the lipase-immobilized microcapsules is 5-10 μm.

[0014] (III) Beneficial effects

[0015] Compared with the prior art, the present invention provides a degradable PP protective film with enhanced weather resistance, having the following beneficial effects:

[0016] 1. Excellent weather resistance: After QUV accelerated aging for 1000 h, the color difference ΔE < 2, and the tensile strength retention rate ≥85%, which is significantly better than commercially available products.

[0017] 2. High-efficiency degradability: In a composting environment for 180 days, the weight loss rate reaches more than 65%, meeting the ASTM D6400 standard.

[0018] 3. Excellent comprehensive properties: Tensile strength ≥45 MPa, haze < 5%, water vapor transmission rate < 5 g / (m2 · 24h), meeting the requirements of high-end packaging and protection.

[0019] 4. Environmental protection and economy: The raw materials are green and environmentally friendly, and the energy consumption of the production process is reduced by 15%, combining social benefits and market competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required in the embodiments. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can be obtained based on these drawings.

[0021] Figure 1 is a schematic structural diagram of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0022] To further illustrate the embodiments, the present invention provides drawings. These drawings are part of the disclosure of the present invention, mainly used to illustrate the embodiments, and can be used to explain the operating principle of the embodiments in conjunction with the relevant descriptions in the specification. With reference to these contents, those of ordinary skill in the art should be able to understand other possible implementation manners and the advantages of the present invention. The components in the drawings are not drawn to scale, and similar component symbols are usually used to represent similar components.

[0023] According to an embodiment of the present invention, a degradable PP protective film with enhanced weather resistance is provided.

[0024] Now, the present invention will be further described in conjunction with the drawings and specific embodiments. As Figure 1 shown, a degradable PP protective film with enhanced weather resistance according to an embodiment of the present invention is composed of the following raw materials in parts by weight: 55 - 65 parts of degradable PP resin, 9 - 12 parts of nano-titanium dioxide / graphene composite powder, 6 - 7 parts of silane coupling agent-modified hindered amine light stabilizer, 6 - 9 parts of tributyl acetylcitrate, 1.5 - 2.5 parts of a compound lubricant of zinc stearate and ethylene bisstearamide, 1 - 2 parts of a compound of hindered phenol and phosphite antioxidants, and 0.5 - 1.5 parts of lipase-immobilized microcapsules.

[0025] The degradable PP resin is a graft copolymer of polylactic acid and PP, with a grafting rate of 3% - 8%. The graft copolymer is prepared by a melt grafting process, and the initiator in the melt grafting process is dibenzoyl peroxide, and its dosage is 0.5% - 1.5% of the total mass of PP and PLA.

[0026] In the nano-titanium dioxide / graphene composite powder, the mass ratio of nano-titanium dioxide to graphene is 3:1, the particle size of the nano-titanium dioxide is 20 - 50 nm, and the number of layers of the graphene is 1 - 3 layers.

[0027] The silane coupling agent-modified hindered amine light stabilizer is prepared by reacting a hindered amine light stabilizer with a silane coupling agent in an organic solvent at 60 - 80 °C for 2 - 4 hours, and the mass ratio of the hindered amine light stabilizer to the silane coupling agent is 1:(0.1 - 0.3).

[0028] The acid value of the tributyl acetylcitrate ≤ 0.2 mgKOH / g, and the chromaticity (APHA) ≤ 20.

[0029] In the zinc stearate and ethylene bisstearamide compound lubricant, the mass ratio of zinc stearate to ethylene bisstearamide is 2:1, and the purity of the zinc stearate ≥ 99%, the melting point of ethylene bisstearamide is 141 - 146 °C. In the hindered phenol and phosphite antioxidant compound, the hindered phenol antioxidant is antioxidant 1076, the phosphite antioxidant is antioxidant 168, and the mass ratio of the two is (0.6 - 1.2):(0.4 - 0.8).

[0030] The lipase-immobilized microcapsules are prepared by emulsion polymerization. The wall material used in the emulsion polymerization is sodium alginate and chitosan, the mass ratio of sodium alginate to chitosan is (1 - 3):1, and the particle size of the lipase-immobilized microcapsules is 5 - 10 μm.

[0031] Organosiloxane has good oxidation resistance and hydrolysis resistance, and can form a protective film on the surface of the PP resin to prevent the intrusion of oxygen and moisture. When the two are used in combination, they can play a synergistic role and significantly improve the weather resistance of the protective film.

[0032] The role of the plasticizer is to improve the flexibility and processing performance of the protective film. Tributyl citrate (TBC) can be selected as the plasticizer. It is an environmentally friendly plasticizer with good compatibility and plasticizing effect, and will not affect the biodegradable performance of the PP resin.

[0033] The lubricant can reduce the friction during the processing of the protective film, improve the processing efficiency and product quality. Calcium stearate can be selected as the lubricant, which has good lubrication performance and thermal stability.

[0034] The antioxidant can prevent the oxidation reaction of the PP resin during processing and use, and extend the service life of the protective film. The hindered phenol antioxidant 1010 and the phosphite antioxidant 168 can be selected and used in combination. The two act synergistically to effectively inhibit the oxidative degradation of the PP resin.

[0035] Light stabilizers can absorb and scatter ultraviolet light, reduce the damage of ultraviolet light to PP resin, and improve the light aging resistance of the protective film. Hindered amine light stabilizer 944 can be selected as the light stabilizer, which has good light stabilizing effect and thermal stability.

[0036] The preparation process of the protective film includes the following steps:

[0037] Raw material pretreatment: Vacuum dry the degradable PP resin at 80 °C for 4 h; After mixing the nano-titanium dioxide or graphene composite powder and the silane-coupled hindered amine light stabilizer in proportion, add an ethanol-water mixed solution, ultrasonically disperse for 30 min, and dry at 60 °C to constant weight. The volume ratio of the ethanol-water mixed solution is 3:1;

[0038] Melt blending: Add the pretreated raw materials to a twin-screw extruder in sequence. The temperature of the first zone of the twin-screw extruder is 180 °C, the second zone is 190 °C, the third zone is 200 °C, the fourth zone is 205 °C, the fifth zone is 210 °C, the screw speed is 180 r / min, the residence time is 3 - 5 min, and then extrude and pelletize;

[0039] Biaxial stretching and forming: After drying the particles at 90 °C for 2 h, extrude them into a thick sheet through a single-screw extruder. The temperature of the single-screw extruder is 190 - 200 °C. Then, conduct longitudinal stretching in a biaxial stretching testing machine. The longitudinal stretching temperature is 120 °C, and the stretching ratio is 3; Then conduct transverse stretching. The transverse stretching temperature is 130 °C, and the stretching ratio is 4. Finally, shape at 140 °C, cool and wind up.

[0040] The length-diameter ratio of the twin-screw extruder is (30 - 40):1, the screw groove depth is 3 - 5 mm, the compression ratio of the single-screw extruder is (2 - 3):1, the screw speed is 30 - 50 r / min. In the biaxial stretching and forming, the thickness of the thick sheet is 0.5 - 1 mm, and the shaping time is 10 - 20 s.

[0041] The tensile strength of the protective film ≥ 45 MPa, the elongation at break ≥ 400%, the haze < 5%, the water vapor transmission rate < 5 g / (m 2 ·24 h). After 1000 h of QUV accelerated aging, the color difference ΔE < 2, and the tensile strength retention rate ≥ 85% for the protective film. In the composting environment for 180 days, the weight loss rate ≥ 65% for the protective film.

[0042] Example 1

[0043] 60 parts of PP-g-PLA, 9 parts of nano-TiO2 / graphene composite powder, 6 parts of HALS-Si, 7 parts of ATBC, 1.5 parts of zinc stearate, 0.75 parts of EBS, 0.8 parts of 1076, 0.5 parts of 168, 1 part of lipase microcapsule.

[0044] Preparation process: Pretreatment, melt blending and biaxial stretching are carried out according to the foregoing steps to obtain the protective film.

[0045] Example 2

[0046] 55 parts of PP-g-PLA, 10 parts of nano-TiO2 / graphene composite powder, 7 parts of HALS-Si, 8 parts of ATBC, 1.8 parts of zinc stearate, 0.9 part of EBS, 1 part of 1076, 0.6 part of 168, 1.2 parts of lipase microcapsule.

[0047] Preparation process: The same as that of Example 1.

[0048] The performance test is shown in the following table

[0049]

[0050]

[0051] In the present invention, unless otherwise clearly defined and limited, the terms "installation", "setting", "connection", "fixation", "swivel connection" and other terms shall be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or integrated; it can be a mechanical connection or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium, and it can be the internal communication of two components or the interaction relationship between two components. Unless otherwise clearly defined, for those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific situations.

[0052] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A degradable PP protective film with enhanced weather resistance, characterized in that: The invention is composed of the following raw materials in parts by weight: 55-65 parts of degradable PP resin, 9-12 parts of nano titanium dioxide / graphene composite powder, 6-7 parts of silane coupling agent modified hindered amine light stabilizer, 6-9 parts of acetyl tributyl citrate, 1.5-2.5 parts of zinc stearate and ethylene bisstearamide compound lubricant, 1-2 parts of hindered phenol and phosphite antioxidant compound, and 0.5-1.5 parts of lipase immobilized microcapsules.

2. The degradable PP protective film with enhanced weather resistance according to claim 1, characterized in that: The degradable PP resin is a graft copolymer of polylactic acid and PP, with a graft rate of 3%-8%. The graft copolymer is prepared by a melt grafting process, and the initiator in the melt grafting process is dibenzoyl peroxide, and its usage is 0.5%-1.5% of the total mass of PP and PLA.

3. The degradable PP protective film with enhanced weather resistance according to claim 1, characterized in that: The mass ratio of nano-titanium dioxide to graphene in the nano-titanium dioxide / graphene composite powder is 3:1, the particle size of the nano-titanium dioxide is 20-50nm, and the number of layers of the graphene is 1-3.

4. The degradable PP protective film with enhanced weather resistance according to claim 1, characterized in that: The silane coupling agent modified hindered amine light stabilizer is prepared by reacting the hindered amine light stabilizer and the silane coupling agent in an organic solvent at 60-80° C. for 2-4 hours, and the mass ratio of the hindered amine light stabilizer to the silane coupling agent is 1:(0.1-0.3).

5. The degradable PP protective film with enhanced weather resistance according to claim 1, characterized in that: The acid value of the acetyl tributyl citrate is ≤0.2 mgKOH / g, and the chromaticity (APHA) is ≤20.

6. The degradable PP protective film with enhanced weather resistance according to claim 1, characterized in that: In the zinc stearate and ethylene bisstearamide compound lubricant, the mass ratio of zinc stearate to ethylene bisstearamide is 2:1, and the purity of the zinc stearate is ≥99%, the melting point of ethylene bisstearamide is 141-146°C, and in the hindered phenol and phosphite antioxidant compound, the hindered phenol antioxidant is antioxidant 1076 and the phosphite antioxidant is antioxidant 168, and the mass ratio of the two is (0.6-1.2):(0.4-0.8).

7. The degradable PP protective film with enhanced weather resistance according to claim 1, characterized in that: The lipase immobilized microcapsules are prepared by emulsion polymerization, the wall materials used in the emulsion polymerization are sodium alginate and chitosan, the mass ratio of the sodium alginate to the chitosan is (1-3):1, and the particle size of the lipase immobilized microcapsules is 5-10 μm.

8. A degradable PP protective film with enhanced weather resistance, characterized in that: The preparation process of the protective film comprises the following steps: Raw material pretreatment: the biodegradable PP resin is vacuum dried at 80°C for 4 hours; nano titanium dioxide or graphene composite powder is mixed with silane coupling agent modified hindered amine light stabilizer in proportion, and then added with ethanol-water mixed solution, ultrasonically dispersed for 30 minutes, and dried at 60°C to constant weight, wherein the volume ratio of the ethanol-water mixed solution is 3:1; Melt blending: add the pretreated raw materials into the twin-screw extruder in sequence, the temperature of the first zone of the twin-screw extruder is 180°C, the second zone is 190°C, the third zone is 200°C, the fourth zone is 205°C, the fifth zone is 210°C, the screw speed is 180r / min, the residence time is 3-5min, and extrusion granulation is performed; Biaxial stretching molding: After the particles are dried at 90°C for 2h, they are extruded into thick sheets through a single-screw extruder at a temperature of 190-200°C. They are then longitudinally stretched in a biaxial stretching testing machine at a temperature of 120°C and a stretching multiple of 3; they are then transversely stretched at a temperature of 130°C and a stretching multiple of 4. Finally, they are shaped at 140°C, cooled and rolled up.

9. The degradable PP protective film with enhanced weather resistance according to claim 8, characterized in that: The aspect ratio of the twin-screw extruder is (30-40):1, the screw groove depth is 3-5mm, the compression ratio of the single-screw extruder is (2-3):1, the screw speed is 30-50r / min, and in the biaxial stretching molding, the thickness of the thick sheet is 0.5-1mm and the shaping time is 10-20s.

10. The degradable PP protective film with enhanced weather resistance according to claim 1, characterized in that: The protective film has a tensile strength of ≥45MPa, an elongation at break of ≥400%, a haze of <5%, and a water vapor permeability of <5g / (m 2 ·24h), after 1000h of QUV accelerated aging, the color difference ΔE of the protective film is less than 2, and the tensile strength retention rate is ≥85%. The weight loss rate of the protective film in a composting environment for 180 days is ≥65%.